DISASTER AND EMOTION IN RICHARD MATHESON’S NOVEL "I AM LEGEND" (University of Bucharest Review. Literary and Cultural Studies Series, 2024)
This article seeks to examine the emotional impact of disaster in the novel I Am Legend (1954) by Richard Matheson, one of the most celebrated writers of science fiction and horror genre in the 20th century. A global pandemic appears to have transformed all people into vampires, except for Robert Neville, the hero, who is immune to the virus. The only human survivor now, he is nightly faced with the massive threat of these infected living and undead vampires, whom the hero kills without mercy day by day, drastically reducing their numbers. While striving to survive at all costs, he tries hard to find a cure for the disease but is finally caught by the living vampires and condemned to death due to his unrestrained violence against them. As the last representative of the ‘old society’, he must relinquish the Earth to the ‘new society’, which is now able to keep the disease in check with a pill. Based on a qualitative research, the analysis begins with an introduction into the concepts of disaster and emotion. It subsequently elaborates on a range of emotions and feelings resulting from the catastrophe in the novel: fear and anxiety; sadness and grief; interest and anticipation, with a view to analyzing the hero’s capability of managing and regulating his emotions and the others’ emotions under psychologically and emotionally distressing circumstances. It is concluded that Neville is not particularly able to effectively manage his emotions, which translates into excessive violence against others. Becoming aware of the consequences of his destructive acts, he accepts his tragic end with courage.
Keywords: disaster; emotion; pandemic; vampire; virus